Brian Raftery: capstone - Raftery, Brian, artist (Colorado State University. Libraries, 2023)
The artist's statement: My design practice revolves around finding fresh unique ways to communicate, whether it be through experimental typographic placements or combining very different mediums within my compositions. My favorite part about the design process is the ability to work from a basic set of rules and then bend those rules in order to creatively express oneself. In my practice, I insure that there is a personal touch seen in my work that you wouldn't see in anyone elses work. While many people can create work that "does the job," I put in the effort to create work that stands out among the rest. With the experience I have had working with clients, I have put in the effort to exceed the set expectations. Having extensive knowledge of the Adobe Suite, especially Photoshop, has allowed me to be able to succeed when working in professional and non-professional environments. Taking time to properly research and brainstorm before diving into any programs is an important part of my process as well. Being able to show potential clients the effort I put into making sure that the designs I create are the best they can be at representing them is something I take pride in. Outside of professional environments, I create work that relates to causes I care about. I have designed multiple posters, as well as a full mock-exhibition, touching on LGBTQ+ topics. As a queer designer, these works mean a lot to me personally. Not only do I learn new techniques and build on my skill set, I get to work on something that I'm truly passionate about. These are the works that I believe best represent my design practice, as they are the perfect display of my current skill set and well as the type of work I like to create aesthetically.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design